The Florida Program for Improving the Training, Evaluation, and Licensure of Educational Personnel - Florida State Dept. of Education, Tallahassee; Florida State Dept. of Education, Tallahassee ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
The program is designed to move the state toward competency-based programs of teacher education, in which program decisions for trainees are made on the basis of demonstration by those trainees of pre-specified competencies. The strategy proposed has two major facets: to provide greater flexibility in the operation of local educational programs and to make local personnel accountable for results. A variety of teacher education programs will be used, and eventually teachers will be required to master only those competencies which have been demonstrated by research to relate to pupil learning. As a first stage, a catalog of teaching competencies will be compiled to serve as a reference for organizing teacher training materials, for analyzing teacher training programs, and for identifying competencies for validation through research projects. Evaluation techniques will be identified or developed which correspond with the specific objectives included in the catalog. A series of research projects are designed to show the relationship between teaching competencies and pupil achievement. The third element in the program is the assembly of protocol materials and materials for training in specific teaching, planning, and supervisory skills; and the final element is the establishment of a statewide program for training teacher trainers. (MFM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Educational Research; Protocol Materials; Teacher Education; Teacher Education Curriculum; Teacher Educator Education